Contributos para o estudo da configuração dos rituais verbais de descortesia em programas de rádio portugueses - Almeida, Carla Aurélia de (2017)
Taking as reference an oral corpus consisting of verbal interactions presented in Portuguese radio phone-in programmes, we analyse the impoliteness in interactive oral discourse, highlighting the semantic and pragmatic aspects to co-construct interactional meaning and referring the particulars face-threatening strategies that take part in the rhetoric devices of offensiveness: verbal threats, rhetorical questions, repetitions, hyperboles, irony, sarcasm and ritual insults. We also analyse the pejorative action that disqualifies the hearer and the functioning of reparatory acts, such as apologies, that occur in interactions of polemic tone.